PD-1/PD-L1 Axis as a Potential Therapeutic Target for Multiple Sclerosis: A T Cell Perspective - Li, HaiXia; Zheng, Chao; Han, Jinming; Zhu, Jie; Liu, Shan; Jin, Tao (Frontiers in Cellular Neuroscience, 2021)
The programmed death protein-1/programmed death ligand-1 (PD-1/PD-L1) axis is a widely studied immune checkpoint that modulates signaling pathways related to T cell activation. The use of PD-1/PD-L1 inhibitors is a promising immune therapy strategy for cancer patients. However, individuals treated with PD-1/PD-L1 inhibitors may develop immune-related adverse events due to excessive immune reactions. Multiple sclerosis (MS) is a chronic demyelinating and neurodegenerative disease of the central nervous system. T cells and the PD-1/PD-L1 axis play vital roles in the pathogenesis of MS. A better understanding of the complex relationship between the PD-1/PD-L1 axis and T cells may extend our knowledge of the molecular mechanisms and therapeutic approaches for MS. In this review, we summarize the most recent findings regarding the role of the PD-1/PD-L1 axis in MS and discuss the potential therapeutic strategies to modulate the expression of PD-1/PD-L1 in MS.